2000
DOI: 10.1007/s001250051547
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight reduction on skeletal muscle UCP2 and UCP3 mRNA expression and UCP3 protein content in Type II diabetic subjects

Abstract: The uncoupling proteins 2 and 3 (UCP2 and UCP3) are probable candidates for underlieing the variability in human energy metabolism. The uncoupling protein genes encode for mitochondrial protein carriers, which uncouple mitochondrial respiration from ATP production and thus stimulates heat production [1]. The UCP2 is ubiquitously expressed in different tissues, whereas UCP3 is mainly expressed in skeletal muscle [2,3]. Furthermore, UCP3 is expressed in a long (UCP3L) and a short (UCP3S) isoform, the latter lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…The reliability of this quantitative method has been previously demonstrated in rats. 20 In humans, it has been reported that a significant muscle reduction of UCP3 mRNA expression was associated with a weight loss 21,22 further illustrating the potential role of UCP3 in the control of weight gain. Interestingly, the capsiateadministrated rats showed a lower weight gain coupled to a decreased abdominal fat content although they were hyperphagic as compared to control animals.…”
Section: Discussionmentioning
confidence: 98%
“…The reliability of this quantitative method has been previously demonstrated in rats. 20 In humans, it has been reported that a significant muscle reduction of UCP3 mRNA expression was associated with a weight loss 21,22 further illustrating the potential role of UCP3 in the control of weight gain. Interestingly, the capsiateadministrated rats showed a lower weight gain coupled to a decreased abdominal fat content although they were hyperphagic as compared to control animals.…”
Section: Discussionmentioning
confidence: 98%
“…We previously demonstrated that, when body weight is stable, UCP3 expression in the skeletal muscle of obese participants is not significantly related to the basal metabolic rate [22]. However, the decreased UCP3 expression repeatedly reported in post-obese patients [23][24][25] suggests that, during the weight loss process, downregulation of UCP3 could lead to energy conservation, thus limiting the extent of weight loss. Therefore, UCP3 is a potential determinant of energy expenditure during weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary findings are also reported. When weight loss is induced by dietary restriction rather than fasting, UCP2 mRNA in vastus lateralis muscle increases slightly [96,101]. Of interest, UCP2 expression in the vastus lateralis muscle of tetraplegic patients is increased by nearly fourfold compared with able-bodied subjects.…”
Section: Fuel Metabolismmentioning
confidence: 99%